Effects of water on a catalytic system for preparation of N-(1, 4-dimethylamyl)-N′-phenyl-p-phenylenediamine by reductive alkylation. Issue 41 (26th June 2018) - Yu, Wenlong; Ding, Junwei; Yu, Shitao; Liu, Fusheng
Abstract : Water could restrain the formation of a Schiff base, reducing the selectivity of 7PPD and aggravating the decrease of catalytic performance. Abstract : Effects of water on a catalytic reaction system for reductive alkylation of p -aminodiphenylamine ( p -ADPA) with 5-methyl-2-hexanone (MIAK) was studied. Platinum nanoparticles supported on activated carbon with high specific surface area were used as catalysts for reductive alkylation reaction under different water content conditions. Schiff base forming data, catalytic activity and stability of the catalysts were investigated under the aforementioned reaction conditions. Fresh and used catalysts were characterized by TEM, SEM, XRD, ICP, laser particle size analysis, N2 physical adsorption and CO chemical adsorption to explore the effects of water on the catalytic reaction system for the ketone/amine reductive alkylation reaction. The characterization results indicated that catalyst support pulverization and Pt loss occurred in the reused catalyst, and the trend was more obvious under the conditions of higher water content. Water in the reaction system could also aggravate the decrease of the catalyst's specific surface area and pore volume, which should be a major reason of the lower catalytic performance.